2020
DOI: 10.1101/2020.05.23.20110932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remdesivir use in patients with coronavirus COVID-19 disease: a systematic review and meta-analysis of the Chinese Lancet trial with the NIH trial

Abstract: Background Coronavirus disease 2019 (COVID-19), caused by the novel coronavirus SARS-CoV-2, has led to significant global mortality and morbidity. Until now, no treatment has proven to be effective in COVID-19. To explore whether the use of remdesivir, initially an experimental broad-spectrum antiviral, is effective in the treatment of hospitalized patients with COVID-19, we conducted a systematic review and meta-analysis of randomized, placebo-controlled trials investigating its use. Methods A rapid search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Taking into account that the study was not powered to evaluate mortality, this is still a positive signal that must be further evaluated in large-scale studies. A meta-analysis with pooled data from the two available RCTs that is still under peer review concludes a statistically significant reduction in mortality (risk ratio [RR], 0.69 [95% CI, 0.49 to 0.99]) ( 71 ). Although the clinical data on remdesivir are not fully published yet, the emergency authorizations and recent approval by the EMA are encouraging, as most other investigational drugs have failed until now ( 72 , 73 ), leaving remdesivir the only antiviral with clinically proven efficacy against COVID-19 to date.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that the study was not powered to evaluate mortality, this is still a positive signal that must be further evaluated in large-scale studies. A meta-analysis with pooled data from the two available RCTs that is still under peer review concludes a statistically significant reduction in mortality (risk ratio [RR], 0.69 [95% CI, 0.49 to 0.99]) ( 71 ). Although the clinical data on remdesivir are not fully published yet, the emergency authorizations and recent approval by the EMA are encouraging, as most other investigational drugs have failed until now ( 72 , 73 ), leaving remdesivir the only antiviral with clinically proven efficacy against COVID-19 to date.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous meta-analysis, we included more studies to assess clinical efficacy [4]. Since the studies involved patients of different baseline ordinal score, the effects may vary across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Its therapeutic effects, adverse events and usage in COVID-19 patients are currently being explored in large-scale randomized controlled trials (RCTs). A recent meta-analysis in a preprint format has only included two RCTs [4]. We aimed to provide a more up-to-date systematic review and meta-analysis to investigate the therapeutic effect and adverse events of remdesivir in severe COVID-19 infections with existing literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Remdesivir has been shown to inhibit SARS‐CoV‐2 replication in human stem cell‐derived intestinal organoids 279 . This potent in vitro activity against SARS‐CoV‐2 has led to a number of clinical trials of intravenous remdesivir in adults hospitalized with COVID‐19 280–287 …”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…Due to the lack of such studies, the authors also stated that remdesivir should not be recommended for the treatment of severe COVID‐19. A third review of pooled evidence from 1141 COVID‐19 patients 287 noted that remdesivir has a modest yet significant reduction in mortality (0.67, 95% CI 0.47–0.96) and significantly improves the time to recovery (3.95 less days, for 3.86 less days to 4.05 less days). The authors concluded that remdesivir may not be sufficient on its own, but in combination with other antivirals or with convalescent plasma may be sufficiently effective 287 .…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%